양조용 적색 포도 품종의 수형에 따른 수체생장, 과실 품질 및 양조적성 - 정성민(Sung Min Jung); 허윤영(Youn Young Hur); 이동훈(Dong Hun Lee); 임동준(Dong Jun Im); 박서준(Seo Jun Park); 정석태(Seok Tae Jeong) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2020)
The cultivars of wine grapes 'Doonuri', 'Narsha', 'Cabernet Sauvignon', and 'Merlot' were cultivated in Modified-T (MT), Modified-T Cane pruning (MTC), and Geneva Double Curtain (GDC) trellises, and the changes in vine growth, fruit and wine characteristics were compared for two years (2018 and 2019). With respect to the vine growth characteristics, the wine grape cultivars cultivated in the GDC trellis were significantly inferior to those cultivated in the MT or MTC trellises. The grape yields of the cultivars cultivated in GDC trellise increased by 1.5 to 2 times cultivated in the GDC trellises compared to those cultivated in the other trellis, however, the fruit characteristics (total soluble solids, titratable acidity, and berry weight) did not differ among the differently cultivated groups. Moreover, the anthocyanin content and red color of the wine were significantly enriched in all red wine grape cultivars cultivated in the GDC trellises.